Sesquiterpene lactone, a potent drug molecule from Artemisia pallens Wall with anti-inflammatory activity - Ruikar, Anjali D; Misar, Ashwini V; Jadhav, Ravindra B; Rojatkar, Supada R; Mujumdar, Arvind M; Puranik, Vedavati G; Deshpande, Nirmala R (Arzneimittelforschung, 2011)
The present study was carried out to investigate the anti-inflammatory activities of bioactive secondary metabolites of Artemisia pallens Wall, an aromatic herb from family Asteraceae. The results provide evidence for the topical anti-inflammatory properties of Artemisia pallens Wall. The compounds were isolated from the acetone extract of the plant material. The isolates were tested on Swiss albino mice using 12-O-tetradecanoyl phorbol-13-acetate (TPA) induced ear edema. One of the molecules from the extract indicated potent anti-inflammatory activity equivalent to indometacin (CAS 53–86–1). Elucidation of the molecular structures by single crystal x-ray diffraction studies revealed the conformational differences that the six membered rings in both the molecules are at an angle of 28.79°. Presence of hydroxy function for compound 2 may be responsible for higher potency.
Keywords: Anti-inflammatory activity; Artemisia pallens; Asteraceae; Mice; Single crystal x-ray structure